Effect Of Dietary Ascorbic Acid On Wound Healing, Susceptibility To Aeromonas Hydrophila Infection And Its Sequential Hematology In The African Catfish, Clarias Gariepinus - E. Erazo, Gregoria (1997)

(untitled)
Two experiments were conducted with African cat fish , Clarias gariepinus ( body weight , 80 - 150g ) , under laboratory conditions . Fish were fed practical -type diets containing different levels of ascorbic acid (0,60,100, 300 and 700 mg/ kg ) . In experiment 1 , small surgical incisions were made in the dorsolateral musculature . Fish were sampled every 4hr over 14 days and histopathological assessment of the wound was carried out . The results showed that irrespective of vitamin levels , epidermis and dermis were almost completely healed except in fish fed deficient of ascorbic acid which exhibit delayed collagen The ascorbic acid concentrations in liver increased significantly as dietary ascorbic acid concentrations increased . However, it gradually decreased until the 14 th day of the experiment. Fibroblast were present at 96h irrespective o f the ascorbic acid level . Skin and muscle at the wound site were almost normal after 6 days in fish f ed 60-7 00 mg of ascorbic acid/kg of diet . In experiment 2 , wounded fish were exposed to live Aeromonas hydrophila by immersion and sampled for histopathologi cal evaluation for 28 days . Fish fed the ascorbic acid - free diet have slower wound repair compared with fish fed diet supplemented with ascorbic acid in the diet. deposition.